Analysis of the Relationship between Road Slope and Total Resistance to Fuel Consumption of Sany Skt 90s Dump Truck - Heri Prabowo; Clara Febriani (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2023)
The purpose of this study was to determine the relationship between road slope and total resistance to Dump Truck fuel consumption. Based on the calculations, the relationship between road slope and fuel consumption is obtained using the regression equation for when loaded Y = 0.0817X +1.831 and when empty Y = 0.0344X + 0.787. While the relationship between total resistance and fuel consumption when loaded with the regression equation Y = 0.0012X +1.8229 when loaded and Y = 0.001X + 0.5789 when empty. The recommended recommendation to reduce dump truck fuel consumption is by improving the road slope according to the standard, which is 8%. After repairing the road slope, the company can save fuel consumption of 87.07 liters/day for 14 dump trucks with an estimated savings of Rp.1,105,764.87 per day. Tujuan penelitian ini untuk mengetahui hubungan kemiringan jalan dan total resistance terhadap konsumsi bahan bakar Dump Truck. Berdasarkan perhitungan, didapatkan hubungan kemiringan jalan terhadap konsumsi bahan bakar menggunakaan persamaan regresi untuk saat bermuatan Y= 0,0817X +1,831 dan ketika kosong Y= 0,0344X + 0,787. Sedangkan hubungan total resistance terhadap konsumsi bahan bakar ketika bermuatan dengan persamaan regresi Y = 0,0012X +1,8229 ketika bermuatan dan Y= 0,001X + 0,5789 ketika kosong. Rekomendasi yang disarankan untuk dapat menurunkan konsumsi bahan bakar dump truck adalah dengan cara perbaikan kemiringan jalan yang sesuai standar, yaitu 8%. Setelah adanya perbaikan kemiringan jalan, perusahaan dapat menghemat pemakaian bakar sebanyak 87,07 liter/hari untuk 14 unit dump truck dengan taksiran hemat sebesar Rp.1.105.764,87 per hari.